Pergeseran Relasi Sosial Akibat Teknologi Komunikasi Dimasa Pandemi Covid-19 Mahasiswa Fakultas Sastra Universitas Muslim Indonesia - Bachrir , Mutmainna; Zelfia, Zelfia; Ahdan, Ahdan (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to describe the phenomenon of social relations among students of the Faculty of Letters, Universitas Muslim Indonesia during the COVID-19 pandemic, and to describe the shift in social relations due to communication technology during the COVID-19 pandemic. This research lasted for one month with 6 (six) informants where they were active students of the literature faculty of the Indonesian Muslim University. The type of research used is descriptive qualitative phenomenological research. The sources of data obtained using observation and interview methods, and documentation as supporting material for data collection. In this study, the author wants to see how the shift in social relations of students whose scope of life is in contact with communication technology on a regular basis due to the Covid-19 pandemic. Social relations are part of human needs that come from the interaction process carried out. In this pandemic period, especially students, who are faced with a situation where structurally and processally experiencing changes that have an impact on the pattern of life. The Covid-19 Virus Pandemic is actually able to shift the lives of students who affect social interactions and social processes by utilizing and developing communication technology (gadgets) during the Covid-19 pandemic so that sometimes they forget their essence as social beings, namely beings who need other people.